Synergistic effect of cocatalytic NiSe2 on stable 1T-MoS2 for hydrogen evolution. Issue 12 (10th February 2021) - Li, Zhen; Ma, Xinzhi; Wu, Lili; Ye, Hongfeng; Li, Lu; Lin, Shuangyan; Zhang, Xitian; Shao, Zhitao; Yang, Yue; Gao, Hong
Abstract : N-doped NiSe2 nanoparticles were selected as the cocatalytic support for 1T-MoS2 nanosheets to construct an efficient and stable heterogeneous 1T-MoS2 /N-doped NiSe2 catalyst for HER. Abstract : Robust and economical catalysts are imperative to realize the versatile applications of hydrogen. Herein, a 1T-MoS2 /N-doped NiSe2 composite was rationally synthesized via a solvothermal method, in which the MoS2 nanosheets have a stable 1T phase structure, and the NiSe2 nanoparticles serve as a cocatalytic support for MoS2 . The nonnegligible electronic couplings between NiSe2 and MoS2 could facilitate the optimization of their electronic structure and then improve the hydrogen adsorption. What is more, the nitrogen dopants in the NiSe2 nanoparticles could intensify the intercalation of ammonium ions in the 1T-MoS2 nanosheets, and further enlarge their interlayer spacing, thus the electrolyte could infiltrate into the catalyst more easily and sufficiently. This work provides a new route for rationally designing highly active and low cost hydrogen evolution reaction (HER) catalysts, and enriches the study of transition metal chalcogenides toward HER.